Claudin 6 is associated with a short survival and a short recurrent free interval in non-small cell lung carcinoma - Soini, Ylermi; Pirinen, Risto; Takasawa, Kumi; Osanai, Makoto; Takasawa, Akira (Polish Journal of Pathology, 2022)
We investigated the expression of claudin 6 in non-small-cell lung carcinomas (NSCLC) by immunohistochemistry. Samples of 164 patients with NSCLC were studied by immunohistochemistry. Claudin 6 was expressed in 42 % of cases. Its expression was significantly more frequent in adeno- than in squamous cell carcinoma (p = 0.002). There was no association between the TNM status and claudin 6 expression. Claudin 6 associated with a poor prognosis of the patients and with a short recurrence-free interval (p = 0.002, p < 0.001). The association with survival had independent prognostic value (p = 0.011). The results show that claudin 6 can be regarded as a marker of poor prognosis in lung cancer. This is different to some other cancers, such as breast and cervical carcinoma suggesting that claudin 6 probably induces other cellular pathways in neoplastic lung cells than in those tumors. In lung cancer, adenocarcinomas were most abundantly positive indicating a higher linkage of claudin 6 to glandular differentiation.